PEER AND TEACHERâS EDITING TO ENHANCE THE COMPETENCE OF ACTIVE AND PASSIVE LEARNERS IN WRITING DISCUSSION TEXTS - Hastuti, Upik (English Education Journal, 2014)
Writing is one of the important parts in teaching a language. The objectives of this study are to find out the significant difference between peer and teacherâs editing in teaching writing discussion texts to active learners, to passive learners, the more effective strategy between peer and teacherâs editing in teaching writing discussion texts among active and passive learners, the significant interaction among studentsâ condition, teaching strategies and writing skill.This study is a quasi experimental research and the design is factorial. In collecting the data, the paired sample t-test and Factorial Analysis of Variance were used to test the hypothesis. The qualitative data were taken from the questionnaires and observation deal with the active and passive learners.The findings showed that there is significant difference between peer and teacherâs editing in teaching writing discussion texts to active learners and so for passive learners,Â  and there is no significant interaction among teaching strategies, studentsâ condition and writing achievement of discussioon tetxs. In conclusion, peer editing strategy is more effective than teacherâs editing strategy. So, peer and teacherâs editing among active and passive learners is significantly effective to enhance studentsâ writing skill of discussion texts.